2013
DOI: 10.1038/srep01774
|View full text |Cite
|
Sign up to set email alerts
|

Climate variability and outbreaks of infectious diseases in Europe

Abstract: Several studies provide evidence of a link between vector-borne disease outbreaks and El Niño driven climate anomalies. Less investigated are the effects of the North Atlantic Oscillation (NAO). Here, we test its impact on outbreak occurrences of 13 infectious diseases over Europe during the last fifty years, controlling for potential bias due to increased surveillance and detection. NAO variation statistically influenced the outbreak occurrence of eleven of the infectious diseases. Seven diseases were associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 54 publications
(57 reference statements)
4
41
0
2
Order By: Relevance
“…Mapping of vulnerabilities to infectious diseases [10] and an assessment of the vulnerability to the risks of infectious disease transmission due to climate change [82] have been undertaken. When researchers studied 2058 outbreaks of 114 infectious diseases occurring in 36 European countries from 1950 to 2009, they found that climatic variations and seasonal changes in the condition of the North Atlantic Oscillation (teleconnection pattern of air pressure leading to warmer/cooler temperatures) influenced the outbreak occurrences of 11 diseases, transmitted through air, water, food, vectors, and rodents [83]. The change in occurrence of infectious diseases in Europe is particularly evident for those transmitted by vectors such as mosquitos, sand flies, and ticks or rodent-borne diseases, and for foodborne diseases as summarized below.…”
Section: Climate-sensitive Infectious Diseasesmentioning
confidence: 99%
“…Mapping of vulnerabilities to infectious diseases [10] and an assessment of the vulnerability to the risks of infectious disease transmission due to climate change [82] have been undertaken. When researchers studied 2058 outbreaks of 114 infectious diseases occurring in 36 European countries from 1950 to 2009, they found that climatic variations and seasonal changes in the condition of the North Atlantic Oscillation (teleconnection pattern of air pressure leading to warmer/cooler temperatures) influenced the outbreak occurrences of 11 diseases, transmitted through air, water, food, vectors, and rodents [83]. The change in occurrence of infectious diseases in Europe is particularly evident for those transmitted by vectors such as mosquitos, sand flies, and ticks or rodent-borne diseases, and for foodborne diseases as summarized below.…”
Section: Climate-sensitive Infectious Diseasesmentioning
confidence: 99%
“…The former study reported multiple climate factors, including solar radiation, air temperature, seas surface temperature, mean radiant temperature, physiologically equivalent temperature and universal thermal climate index 1 to be positively associated with the occurrence of measles, while relative humidity and rainfall were inversely associated with the occurrence [56]. The latter study found that measles outbreaks were associated with winter positive phases of NAO index in northern Europe and with positive values of summer NAO in Europe [26]. Positive and negative NAO represent pressure abnormalities and temperature and precipitation changes extending from eastern North America to western and central Europe.…”
Section: Air-borne Diseasesmentioning
confidence: 94%
“…The effects of climatic conditions on common VPID are summarized in TABLE 1. A recent study suggested climate variability influenced the occurrence of all types of infectious diseases such as air-, water-, vector-and food-borne diseases [26]. UVR exposure may affect immune response to vaccination or reinfection [27].…”
Section: Impacts Of Climate Variability and Uvr On Vpidmentioning
confidence: 99%
See 2 more Smart Citations